Kontribusi Penyadapan Pinus Terhadap Pendapatan Masyarakat Desa Gantarang, Sinjai - Nurul Mukhlishah; Jusmin Jusmin; Agus Salim Syam; Dian Mirnawaty Sultan (Program Studi Kehutanan Fakultas Pertanian Universitas Islam Makassar, 2024)
This study aims to analyze the factors that influence pine resin production, income of tappers, and the contribution of tapping activities to household income in Gantarang Village. The research used a quantitative approach with survey methods, interviews, and direct observation of 15 respondents of pine resin tappers. Data collected included sap production, tapping costs, revenue, and income from other sectors. Analysis was conducted descriptively and quantitatively to evaluate the contribution of tapping to total household income. The results showed that pine resin production is influenced by internal factors such as tree health, diameter, and genetics, as well as external factors such as tapping methods and tapping location distance. The average annual income from tapping reached IDR 23,267,200, contributing 37.36% to total household income. Income from other sectors, especially agriculture, contributed more, at 62.64%. Overall, tapping activities provide significant benefits as an additional source of income for farmers, especially when facing the risk of crop failure due to climate change. The implications of this study indicate the importance of pine resin tapping as part of rural communities' income diversification. Optimizing production and accessibility of tapping locations through government support can increase the sector's contribution to the household economy, thereby supporting the economic sustainability of local communities.